2002
DOI: 10.1590/s1517-83822002000400005
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in soil in response to different plans, phosphate fertilizers and liming

Abstract: The diversity of bacterial isolates from soil in response to different plants (control, Brachiaria ruziziensis and Cajanus cajan), fertilization (control, simple superphosphate and rock phosphate) and liming (with and without lime) was evaluated. Phenotypic and physiological characteristics of the isolates were recorded and organized in a file to identify the bacteria. Among the isolates, 95% were Gram-positive and 5% Gramnegative rods. Soil cultivated with B. ruziziensis favored the nonsporing Gram-positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 32 publications
3
16
1
2
Order By: Relevance
“…In other studies to assess soil diversity in tropical regions Bacillus, Micrococcus and Enterobacter genera were found, being the latest the most abundant genera, but Lactobacillus genus was detected as well (23).…”
Section: Resultsmentioning
confidence: 91%
“…In other studies to assess soil diversity in tropical regions Bacillus, Micrococcus and Enterobacter genera were found, being the latest the most abundant genera, but Lactobacillus genus was detected as well (23).…”
Section: Resultsmentioning
confidence: 91%
“…Soil microorganisms and their metabolisms are sensitive indicators of soil fertility and environmental changes (Wang et al 2007). Bacterial, fungal, and actinomycetes populations of soils are functions of the soils' organic carbon contents (Entry et al 2008); a pH at the upper end of the normal range often has been observed to encourage microbial growth (Silva and Nahas 2002). However, heavy metals might alter the population size, diversity, and activities of microbes in the receiving soils (Rajapaksha et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Each isolate was examined by Gram staining and endospore staining [13]. Most of the biochemical tests were performed according to MacFaddin [14].…”
Section: Morphological and Biochemical Testmentioning
confidence: 99%